High-sensitivity C-reactive protein/albumin (hs-CRP/albumin) ratio as a predictor of deterioration of clinical outcome in central nervous system infections - Hayati, Hanifah Fajarisna; Satiti, Sekar; Paryono, Paryono; Intansari, Umi; Sutarni, Sri; Subagya, Subagya; Indarwati, Indarwati; Setyopranoto, Ismail (Universitas Gadjah Mada, 2023)
Central nervous system (CNS) infections such as encephalitis, meningitis, or myelitis have high morbidity and mortality in Indonesia. High sensitivity C-reactive protein (hs-CRP) is a sensitive marker of acute inflammation, while albumin is the most abundant protein component in plasma and cerebrospinal fluid (CSS). Infection triggers an inflammatory response so that an increase in the hs-CRP/albumin ratio (CAR) can be a predictor of worsening clinical outcome in patients with CNS infections. However, studies examining the predictor value of serum and CSF CAR on worsening clinical outcomes of patients are limited, particularly in CNS infections. The purpose of this study was to prove the CAR as a predictor of worsening clinical outcome in patients with CNS infections. It was an observational study using a prospective cohort design. Fifty subjects recruited until October 2021 at Dr. Sardjito General Hospital were involved. The multivariate regression analysis showed that serum CAR (OR=3.604; 95%CI=1.487-8.736; p =0.005) could be a single predictor. However, by combining three variables, namely serum CAR, CSF CAR, and decreased consciousness at admission, could be a stronger predictor of worsening clinical outcome in patients with CNS infection (AUC = 97.1%; 95%CI = 0.929-1.00; p <0.001). The optimal cut-off value for serum CAR was 1.35 (Youden index = 0.88, sensitivity = 96%, specificity = 92%) while for CSF CAR was 0.14 (Youden index = 0.60, sensitivity = 76%, specificity = 84%). In conclusion, a combination predictive model of three variables, namely serum CAR, CSF CAR, and awareness at admission can be a stronger predictor of clinical outcome in patients with CNS infection than serum CAR alone.